Methylenetetrahydrofolate reductase and transcobalamin genetic polymorphisms in human spontaneous abortion: biological and clinical implications - Zetterberg Henrik (BMC, 2004)
Abstract The pathogenesis of human spontaneous abortion involves a complex interaction of several genetic and environmental factors. The firm association between increased homocysteine concentration and neural tube defects (NTD) has led to the hypothesis that high concentrations of homocysteine might be embryotoxic and lead to decreased fetal viability. There are several genetic polymorphisms that are associated with defects in folate- and vitamin B12-dependent homocysteine metabolism. The methylenetetrahydrofolate reductase (MTHFR) 677C>T and 1298A>C polymorphisms cause elevated homocysteine concentration and are associated with an increased risk of NTD. Additionally, low concentration of vitamin B12 (cobalamin) or transcobalamin that delivers vitamin B12 to the cells of the body leads to hyperhomocysteinemia and is associated with NTD. This effect involves the transcobalamin (TC) 776C>G polymorphism. Importantly, the biochemical consequences of these polymorphisms can be modified by folate and vitamin B12 supplementation. In this review, I focus on recent studies on the role of hyperhomocysteinemia-associated polymorphisms in the pathogenesis of human spontaneous abortion and discuss the possibility that periconceptional supplementation with folate and vitamin B12 might lower the incidence of miscarriage in women planning a pregnancy.